Knowledge and Skills of Social Workers in Handling Children in Conflict with Law in Indonesia - Ellya Susilowati (Asian Social Work Journal, 2018)
This study aims to examine how the knowledge and skill of Social Workers in handling Children against Law (ABH) in Indonesia. Social Worker is a profession mandated by Law No. 11 of 2012 concerning the Juvenile Criminal Justice System has some duties, among others, such as assisting the recovery process and changes in Children behavior; giving consideration to law enforcement officers for handling children social rehabilitation; accompany the delivery of Children to their parents, government agencies or community institutions; and approach the community to be willing to accept the children in their social environment. This study used a qualitative approach with descriptive methods for six social workers who carried out tasks in Cianjur regency, West Java. Data collection techniques used interviews, observation and documentation studies. The results indicated that the knowledge and skills of Social Workers in carrying out the tasks of handling ABH still had some limitations, especially in the application of working skills with ABH. The recommendations of this study are: 1) Education and Training Center in the ABH training for Social Workers needs to increase knowledge and skills about social rehabilitation; 2) Children social workers conduct regular discussions and sharing on the competence of social work related to the handling ABH.